Isadora Duncan’s Dance in Russia: First Impressions and Discussions, 1904–1909 - Yushkova, Elena (Journal of Russian American Studies, 2018)
This article analyzes the ways in which Isadora Duncan’s dance oeuvre was perceived in Russia by different sections of the literati and the intelligentsia. It examines reactions from diverse groups, including Symbolist poets, Russian intellectuals, and choreographers, highlighting how Duncan’s work aligned with contemporary artistic movements. Her rejection of classical ballet's rigidity, emphasis on natural movement, and philosophical approach resonated with Russia’s modernist tendencies. Although Duncan’s tours spanned the early 1900s prior to the Russian Revolution and resumed in the 1920s when she lived and worked in the Soviet Union, Yushkova argues that it was during the 1904–1909 period that Duncan’s performances were very influential on the development of Russian ballet, theater, literature, and dance criticism, and it is these performances that are the particular focus of this article. .